2020
DOI: 10.1002/jcp.29843
|View full text |Cite
|
Sign up to set email alerts
|

JunB can enhance the transcription of IL‐8 in oral squamous cell carcinoma

Abstract: Proteasome inhibitor MG132 was shown to enhance the secretion of interleukin 8 (IL-8) by various cells. The enhancement is regulated by the transcription factor activator protein-1 (AP-1) at the transcriptional level. AP-1 is a dimer formed by AP-1 family proteins. The purpose of the present study was to explore the combinations of the AP-1 family proteins that contribute to MG132-driven IL-8 secretion. Oral squamous cell carcinoma-derived cell lines, Ca9-22 and HSC3, were used to demonstrate their response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…SCENIC analysis identified the upregulation of several proto-oncogenic TFs CEBPA, JUNB, and KLF4 (ref. [16][17][18] ), and tumor suppressor TFs GRHL1 and RCOR1 (ref. 19,20 ) in the TC (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SCENIC analysis identified the upregulation of several proto-oncogenic TFs CEBPA, JUNB, and KLF4 (ref. [16][17][18] ), and tumor suppressor TFs GRHL1 and RCOR1 (ref. 19,20 ) in the TC (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, interfering with the expression of c-Jun could effectively rescue the above phenomena. Furthermore, previous studies have revealed that the transcription factor c-Jun not only regulates the secretion of IL-8 [ 39 41 ] but also acts as a key transcription factor that regulates the secretion of other essential immunoregulatory factors, such as VEGF, PDGFA and HGF, by MSCs [ 20 ]. Abnormal differentiation and a decline in the immunoregulatory capacity of MSCs have been found in many autoimmune diseases, such as AS [ 21 , 42 , 43 ], rheumatoid arthritis (RA) [ 44 46 ], and systemic lupus erythematosus (SLE) [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCENIC analysis identified the upregulation of several proto-oncogenic TFs CEBPA, JUNB, and KLF4 (ref. [18][19][20] ), and tumor suppressor TFs GRHL1 and RCOR1 (ref. 21,22 ) in the tumor core (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%